Passivity-based control of a pulse-width mode operated digital hydraulic drive. (July 2019) - Kogler, Helmut; Schöberl, Markus; Scheidl, Rudolf
Digital hydraulics offers a cost-effective and robust opportunity to replace expensive and sensitive hydraulic servo valves for cylinder drives. If the digital directional valves are operated in pulse-width mode at a constant switching frequency, the mean flow rate through the valves into the actuator is controlled by the duty ratio of the pulse-width-mode signal. However, for a proper implementation of digital hydraulic linear drives, some adaptions must be made compared to common cylinder drives. In this article, a gas-loaded accumulator is used in order to tune the dynamics of the system for a smooth behavior of the drive, which is generally nonlinear. An energy-based controller according to the passivity concept in combination with a load observer is presented. Simulations show the achievable performance.